Spine injuries characterization by computed tomography in canines in Lima, Peru - Shimose C., Patricia (2018)
The objective of this study was to characterize spine injuries in dogs by computed tomography. The tomographic diagnoses were related to the demographic characteristics of dogs under study (sex, size, breed, and age). A total of 79 tomographic diagnoses were evaluated between June 2010 and July 2014. The results showed a greater frequency of lesions in males of defined breed, medium size and in the age group of 4-7 years. Twentytwo tomographic diagnoses were obtained, the most frequent being medial disc herniation (32.8%, 26/79) and laminar calcification of the dural sac (11.4%, 9/79). A total of 115 lesions were identified in the spine, the lower spine being more affected (48.7%, 56/115). At the level of the intervertebral spaces, the thoracic region T12-T13 presented the largest number of lesions (14%, 16/115), especially discopathies.